Rash decisions: Unmasking a risk phenotype in adults with persistent delayed penicillin allergy sensitized during historic infection with Epstein-Barr virus - Fionnuala Cox, BA Hons, PhD, MB, BCh, BAO, MRCPI, FRCPath; Natasha E. Holmes, MBBS, PhD; Jamie Lee Waldron, MD; Jason A. Trubiano, MBBS, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: Penicillin-associated exanthems in the setting of infectious mononucleosis caused by Epstein-Barr virus (EBV) are often viewed as a transient event, not a true allergy. Recent evidence challenges this and suggests that a notable subset of patients retain penicillin hypersensitivity. Objective: We investigated the occurrence and predictors of persistent adulthood hypersensitivity in those with penicillin-associated rash occurring in the setting of EBV infection. Methods: Retrospective analysis of data of patients referred for penicillin allergy testing to an Australian tertiary-care hospital captured from 2015 to 2023 was carried out. Results: Of 2066 patients, 23 (1%) had penicillin-associated rash during an historic EBV infection; 16 (70%) were female; and median (interquartile range) age was 18 (16-20) years at index reaction and 38 (33.5-57) years at allergy testing. Skin prick testing and delayed intradermal testing to a penicillin panel were performed, followed by oral provocation challenge in those testing negative. Persistent sensitization was shown in 6 (26%) of 23; 4 (67%) of 6 positive delayed intradermal testing; and 3 (50%) of 6 had positive oral challenge test. Notably, 5 (83%) of 6 had a severe maculopapular exanthem with facial swelling, including 2 (33%) of 6 with probable drug reaction with eosinophilia and systemic symptoms (aka DRESS) during the index reaction, compared to 0 of 17 in patients tolerating penicillin on reexposure. Conclusion: This study highlights the requirement of allergy testing in adult patients reporting a penicillin-associated severe maculopapular exanthem in the setting of EBV, even if it occurred during childhood or adolescence.